MODERN METHODS OF TEACHING ENGLISH IN POLYTECHNICUM - Rashidova Gulshod Zarifovna (World Scientific Research Journal, 2025)
Abstract: The field of English language teaching has undergone significant transformations due to advancements in technology and pedagogical theories. This study explores modern methods of teaching English in Polytechnicum, emphasizing communicative approaches, technology integration, and student-centered learning. The findings indicate that interactive and digital methodologies improve student engagement and language acquisition.